2019
DOI: 10.1542/peds.2019-0674
|View full text |Cite
|
Sign up to set email alerts
|

Multidisciplinary Engagement Increases Medications in-Hand for Patients Hospitalized With Asthma

Abstract: BACKGROUND: Asthma exacerbations in children are a leading cause of missed school days and health care use. Patients discharged from the hospital often do not fill discharge prescriptions and are at risk for future exacerbations.METHODS: A multidisciplinary team aimed to increase the percentage of patients discharged from the hospital after an asthma exacerbation with their medications in-hand from 15% to 80%. Tools from the model of improvement were used to establish a process map, key driver diagram, and ite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Many existing bedside medication delivery programs in the literature are standalone or targeted to specific populations, mainly based on readmission penalties via HRRP services and discharge diagnoses 12,21,22 . To our knowledge, this is the first study to examine whether reducing travel and financial barriers to obtaining medications reduces readmissions based on comorbidities and medical complexity, as well as primary disease diagnosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many existing bedside medication delivery programs in the literature are standalone or targeted to specific populations, mainly based on readmission penalties via HRRP services and discharge diagnoses 12,21,22 . To our knowledge, this is the first study to examine whether reducing travel and financial barriers to obtaining medications reduces readmissions based on comorbidities and medical complexity, as well as primary disease diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Many existing bedside medication delivery programs in the literature are standalone or targeted to specific populations, mainly based on readmission penalties via HRRP services and discharge diagnoses. 12,21,22 To our knowledge, this is the first study to examine whether reducing travel and financial barriers to obtaining medications reduces readmissions based on comorbidities and medical complexity, as well as primary disease diagnosis. We found that providing prescriptions and combining a subsidy to reduce financial burdens lowers readmissions compared with controls and simply providing medicines; focusing on patients with 0 or ≥ 4 comorbidities provided the greatest impact.…”
Section: Discussionmentioning
confidence: 99%